Γ-Fe2O3 magnetic nanoparticle functionalized with carboxylated multi walled carbon nanotube for magnetic solid phase extractions and determinations of Sudan dyes and Para Red in food samples. (1st March 2018) - Kılınç, Ersin; Çelik, Kadir Serdar; Bilgetekin, Havin
Highlights: - γ-Fe2 O3 (maghemite) and carboxylated-multi walled carbon nanotube (cMWCNT) was used for the magnetic solid phase extraction. -Sudan I, II, III, IV, Para Red, Sudan Black B and Sudan Red 7B were determined in chilli products. -The cMWCNT-γ-Fe2 O3 can be reused at least 20 times without a significant loss of the sorption capacity. Abstract: Hybrid nanostructures composed of γ-Fe2 O3 (maghemite) and carboxylated-multi walled carbon nanotube (cMWCNT) were used for the magnetic solid phase extractions and determination of Sudan I, II, III, IV, Para Red, Sudan Black B and Sudan Red 7B in chili products. High performance liquid chromatography (HPLC) was employed for the measurements. Limit of quantification (LOQ) values were found in the range 0.44–2.82 ng mL −1 for analytes. The best extraction parameters were determined as pH 8.0, 40 mg of magnetic nanoparticle, 4.0 min of contact time, 0.3 mL desorption by acetonitrile. The samples were dissolved in acetone-dichloromethane-methanol (3:2:1, v/v/v) and diluted with acetonitrile-methanol (v/v; 80:20) before the method was applied. Concentrations of Sudan dyes and Para Red were determined in four samples of chili powder from less than LOQ to 31.21 ± 1.6 ng g −1, two samples of chili tomato sauces (lower than LOQ) and two samples of ketchup (lower than LOQ).